Understanding asthma: a study to evaluate the impact of an educational computer program on children's knowledge and selfmanagement skills - McPherson, Amy (2003)
Childhood asthma is an extensive problem and is particularly pronounced in the UK. Asthma can restrict activities, cause school absence and can be the source of considerable stress in both children and their parents. Mortality is rare and preventable, although poor perception of symptoms and delay in seeking medical attention are strong risk factors for a fatal asthma attack. Self- management actively involves the child in their own healthcare and entails monitoring symptoms and responding accordingly and has been linked to better outcomes. This can be facilitated by health education.